Предмет: Алгебра,
автор: DimaBrodski
2(x+1)²+3(x-1)² = 5(x-1)(x+1)-4.
ДОПОМОЖІТЬ ПАЖАЛУСТА
vv8002223:
Формула сокращённого умножения
Ответы
Автор ответа:
2
Ответ:
2(x+1)²+3(x-1)²=5(x-1)*(x+1)=4
(a+b)²=a²+2ab+b²
2(x²+2x+1)+3(x-1)²=5(x-1)*(x+1)-4
(a-b)²=a²-2ab+b²
2(x²+2x+1)+3(x²-2x+1)=5(x-1)*(x+1)-4
(a-b)(a+b)=a²-b²(a-b)(a+b)=a²-b²
2(x²+2x+1)+3(x²-2x+1)=5(x²-1)-4
2x²+4x+2+3(x²-2x+1)=5(x²-1)-4
2x²+4x+2+3x²-6x+3=5(x²-1)-4
2x²+4x+2+3x²-6x+3=5x²-5-4
5x²+4x+2-6x+3=5x²-5-4
5x²-2x+2+3=5x²-5-4
5x²-2x+5=5x²-5-4
5x²-2x+5=5x²-9
-2x+5=-9
-2x=-9-5
-2x=-14|:2
x=7
Похожие вопросы
Предмет: Русский язык,
автор: peee3ksyxMusevna
Предмет: Українська мова,
автор: g1aresSVEnaNatyaE
Предмет: Русский язык,
автор: E1lizavetusyk
Предмет: Математика,
автор: SVETLANASAMSUNGj1ry
Предмет: История,
автор: Аноним